PENGARUH PUSH FACTORS DAN PULL FACTORS TERHADAP TOURISM INTENTION WISATA PERKOTAAN - Rahadatul Aisyi, Syakirah Cahya; Ekasari, Ayu (STMIK Widuri Jakarta, 2025)
Urban tourism refers to the development of tourism in which tourist destinations are located within urban areas, where city zones, specific locations, urban elements, and even the city itself become tourism commodities. The purpose of this study is to analyze the positive influence of push factors on pull factors, pull factors on tourism intention, and push factors on tourism intention. The sampling method used in this study is purposive sampling, with a total of 190 respondents. The data were analyzed using the Structural Equation Modeling (SEM) method. The results show that there is a positive and significant influence of push factors on pull factors, pull factors on tourism intention, and push factors on tourism intention. These findings indicate that all three variables are positively and significantly interrelated.